Willingness of island community to participate in the waste-to-wealth program: A case study in Teluk Renjuna, Tumpat, Kelantan, Malaysia - Mohamad Pirdaus Yusoh; Amal Najihah Muhamad Nor; Kamarul Ariffin Hambali; Normah Abdul Latip; Muhamad Azahar Abas (Malaysia Institute of Planners, 2024)
This manuscript explores Teluk Renjuna communities’ willingness to participate in the waste-to-wealth program. Waste-to-wealth is an initiative to reduce the environmental impact of waste disposal. The total number of respondents who participated in this study was 118 respondents. Analysis indicated a reasonable waste disposal practice among respondents, with moderate knowledge and high awareness of the waste-to-wealth program. Besides that, this study found no significant sociodemographic impact on the knowledge and awareness of respondents on the waste-to-wealth program, except for age, income, and marital status. A Pearson Correlation test assessed the significance between knowledge, awareness, practices, and willingness. The results indicated a weak relationship between practices and willingness. A moderate relationship was found between knowledge and willingness, and a strong relationship was observed between awareness and willingness. The findings of this study are crucial to help government agencies or NGOs in planning suitable waste-to-wealth programs for the island community.